Minor grip: on the constitution of morality, agency and affectivity with technology - Bakhtiar, Siavash (2018)
The purpose of this thesis is to establish a conversation between Bruno Latour and the work of contemporary philosophers and critical theorists in order to develop their respective approaches to articulate a critical theory about technology. To analyse these different perspectives, the thesis follows a conceptual framework based on what Latour calls the “principle of symmetry” between human and non-humans actants that take part in the constitution of what we call society. Through focusing on different “thing theories,” the thesis works to recuperate some of these concepts and practices to enrich my own conceptual toolbox. Each chapter focuses on a particular case study – the revolving door, the Automated Public Toilet, barbed wire and the smartphone – that gives me the ground where I put at test these different perspectives to see if they can be good theoretical allies to give more space in critical theory for what Latour calls its “missing masses.”